Future university in present times: Autonomy, governance and the entrepreneurial university - Eduardo Ibarra-Colado (Management Revue, 2007)
The paper discusses the main challenges confronted by Mexican government agencies and universities to deal with the model implemented since the late 1980s in the context of neoliberalism and globalization. Such challenges are associated with the tendencies observed at three levels. First, the transformation of the sense and content of the autonomy regime of the university and its legal principles. Secondly, the emergence of governance as a strategic condition to perform institutional ends and projects in a market driven context. Finally, the gradual conformation of the entrepreneurial university under new organizational arrangements through which it is trying to perfom their functions effectively and legitimately to fulfill current market and economic demands. The paper concludes by discussing some alternative arrangements, thus advocating the transformation of the university system in order to confront the challenges resulting from new emerging contexts, but without abandoning its commitment to social development and equity and its historical role as a main cultural institution for society.
Keywords: 650; globalization; autonomy; governance; participation